Diseño de un centro de spa para desarrollar el turismo en Calceta, provincia de Manabí. - Andrade Chancay, Óscar Luis (2013)
The objective of this research was to make a design of a SPA in order to create a tourist alternative designed to meet the needs of relaxation contributing to the development of the tourist resort of Canton Bolívar, taking into account the new trends of the visitor not only the leisure but also find time to rest due to stress of working life for which we developed the baseline of Canton, was determined supply and demand for spa services, technical study was analyzed to determine the location, load capacity, size of building is 250 m2, the environmental impact study determined the Leopold matrix application; were determined negative environmental impacts of the proposal, both in the construction of the SPA center as start-up, in terms of the economic and financial viability the proposal is feasible as indicated by the results of Cash Flow, Net Present Value (NPV), Internal Rate of Return (IRR) and the Period of Return on Investment (PRI ).